Methodology for deleting lessons that develop on the basis of concentrated training technology in beginner classes - Iminova Khurshida Mukhtarovna (Peerian Journals Publishing, 2023)
this article provides information on the methodology for deleting developing classes based on concentrated talim technology in beginner classes , identification of basic skills, design of target classes, the use of technology to enhance learning experience.
Keywords: concentration; technology; beginner class; design